Postcolonial perspectives on 'development' - Aram Ziai (University of Bonn, Center for Development Research (ZEF), 2012)
The article deals with postcolonial works in the field of development theory and policy beyond the widely discussed post-development approaches. After identifying four analytical strategies typical for postcolonial studies, it examines the works in question. Particular attention is given to the criticism that postcolonial works would neglect material practices. The article concludes that for many works this criticism is not justified, but that the empirical engagement of postcolonial approaches with institutions and processes in development policy is often inaccurate, superficial and incomplete. 'Development studies does not tend to listen to subalterns and postcolonial studies does not tend to concern itself with whether the subaltern is eating' (Sylvester 1999: 703). Christine Sylvester's well-known characterisation of the relationship between development studies and postcolonial studies may be somewhat exaggerated, it is, however, based on a sharp observation. This relationship also constitutes the topic of this article. The article's objective is twofold: on the one hand it aims to provide a - far from exhaustive - survey of works from the area of postcolonial studies that deal with 'development'. Usually this type of work is associated with the post-development school, which has been widely discussed by now, but here the focus is on other authors beyond post-development. On the other hand, the article will deal with one of the central points of criticism which has been raised against postcolonial studies: that they neglect material practices. This criticism shall be examined on the grounds of the postcolonial works in the field of 'development'. For a start, it needs to be clarified what is meant by postcolonial studies and by 'development' - and why the concept is placed in quotation marks. Therefore the first section of the article deals (very briefly) with the concept of development and the second one (equally superficially) with the field of postcolonial studies. In the latter, specifically postcolonial questions and strategies of analysis will be examined, in order to achieve some orientation faced with the multitude of works and approaches in this field. Subsequently the focus will be on the relationship between development studies and postcolonial studies. Regarding the accusation of neglecting material practices and the strategies identified beforehand, a number of postcolonial works in the area of 'development' theory and policy will be scrutinized.
Keywords: 330; postcolonial studies; development policy